Are Altmetric.com scores effective for research impact evaluation in the social sciences and humanities?. Issue 1 (February 2021) - Yang, Siluo; Zheng, Mengxue; Yu, Yonghao; Wolfram, Dietmar
Highlights: A conceptualization and an operationalization framework of effectiveness of Altmetric.com scores are proposed. Altmetric.com scores can help to reflect multidimensional impact but are not currently effective indicators. The strongest indicator of Altmetric.com scores to reflect scholarly impact of SSH researches is Readers. Abstract: Altmetric.com is one of the leading and widely used commercial providers of altmetrics. Altmetrics is a broad term that encapsulates the collection of multiple digital indicators related to scholarly work (NISO, 2016). In this paper, the group of altmetrics provided by Altmetric.com is called Altmetric.com scores. This study assesses whether Altmetric.com scores are currently effective indicators to evaluate the research impact of social sciences and humanities (SSH). This research covers 1, 253, 028 records from the SSCI and A&HCI for five years (2013–2017), three publication types (articles, reviews, and proceedings papers), and 10 altmetrics provided by Altmetric.com to test the effectiveness of Altmetric.com scores through four proposed dimensions, including transparency, fairness, availability, and validity. Results show that the transparency of Altmetric.com scores is underexposed. And Altmetric.com scores favored English publications authored by North American researchers. Except for Altmetric attention score, Posts, Readers, and Tweeters, the data presence of most Altmetric.com scores was insufficient. As to research impact, Altmetric.com scores can help to reflect different impacts of SSH research. Overall, the results suggest that Altmetric.com scores are not yet sufficiently effective for evaluating the impact of SSH research though they can provide new insights into impact evaluation.